Well-Being in Psoriasis: Weighting its Components Using Best-worst Scaling Methodology - Esteban Daudén; Isabel Belinchón; Elena Colominas-González; Pablo Coto; Pablo de la Cueva; Fernando Gallardo; Jose Luis Poveda; Esther Ramírez; Sandra Ros; Ricardo Ruíz-Villaverde; Isabel Cabezas; Luis Lizán (Dermatology and Therapy)
Abstract Introduction The Inpsight Project, established in 2021, aimed to define the concept of well-being in patients with psoriasis from a holistic perspective. Well-being was defined as a multi-dimensional concept that includes achieving emotional balance, having adequate overall health and control of the disease, enjoying positive social relationships, and being satisfied with disease care. However, while these components are recognized as integral to the concept, their relative contribution to achieving optimal well-being remains unclear. To address this gap, the present study aimed to determine the relative weight of each component in contributing to optimal well-being, focusing on a Spanish population. Methods An observational, descriptive, cross-sectional study was conducted in Spain using best-worst scaling (BWS). Two questionnaires were developed: one addressed to patients (33 item) and the other to healthcare professionals (HCPs) (18 item). The questionnaires collected sociodemographic and clinical (patients)/occupational (HCP) characteristics of the participants and the BWS scenarios. The 20 components of well-being were randomly distributed across 76 scenarios, with each component paired with others four times to ensure a comprehensive evaluation of all possible combinations. Participants assessed 9–10 randomly selected scenarios and identified the components they considered most (best) and least (worst) important for achieving optimal well-being. Results A total of 87 HCPs and 152 patients with psoriasis participated in the study. The five key components for patients were pain (P: 100.00), stress (P: 98.74), treatment satisfaction (92.21), itching (72.05), and lesions in functional locations (P: 69.09). From a HCP perspective, the most important components were mood disorders (100.00), pain (69.39), lesions in functional locations (49.34), self-esteem (49.24), and stigmatization/shame (45.22). Conclusions This study highlights the differences between patients and HCPs in their perception of the relative importance and relevance of the components contributing to the well-being of patients with psoriasis. Future research should focus on understanding the cumulative impact of psoriasis on patient well-being.